2006
DOI: 10.1118/1.2350705
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of three‐dimensional angiographic data obtained by self‐calibration of multiview imaging

Abstract: Stroke is one of the leading causes of death in the U.S. The treatment of stroke often involves vascular interventions in which devices are guided to the intervention site often through tortuous vessels based on two-dimensional (2-D) angiographic images. Three dimensional (3-D) vascular information may facilitate these procedures. Methods have been proposed for the self-calibrating determination of 3-D vessel trees from biplane and multiple plane images and the geometric relationships between the views (imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Methods of pose characterization include the use of stereoscopic tracking systems to monitor mechanical motion 25 and, more commonly, image-based methods that operate directly on projection data acquired either from a prior calibration 2,18,23,24 or simultaneous with imaging. 20,28 The form of the geometric characterization can consist of a projection matrix describing the linear relationship between 3D voxel coordinates and 2D pixel coordinates, 19,24 or a set of geometric parameters describing degrees of freedom in the imaging system ͑e.g., source and detector positions, detector rotation angles, etc.͒. 18 Perhaps the simplest method for image-based geometric calibration of a CBCT system uses a single ball bearing ͑BB͒ placed near the isocenter of the rotational gantry to characterize the location of the "piercing point" ͑i.e., the point at which the isocenter projects on the detector plane͒ as a function of gantry angle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods of pose characterization include the use of stereoscopic tracking systems to monitor mechanical motion 25 and, more commonly, image-based methods that operate directly on projection data acquired either from a prior calibration 2,18,23,24 or simultaneous with imaging. 20,28 The form of the geometric characterization can consist of a projection matrix describing the linear relationship between 3D voxel coordinates and 2D pixel coordinates, 19,24 or a set of geometric parameters describing degrees of freedom in the imaging system ͑e.g., source and detector positions, detector rotation angles, etc.͒. 18 Perhaps the simplest method for image-based geometric calibration of a CBCT system uses a single ball bearing ͑BB͒ placed near the isocenter of the rotational gantry to characterize the location of the "piercing point" ͑i.e., the point at which the isocenter projects on the detector plane͒ as a function of gantry angle.…”
Section: Introductionmentioning
confidence: 99%
“…2 In general, geometric calibration relates the 3D coordinates ͑x , y , z͒ of voxels in the reconstructed image to the 2D coordinates ͑u , v͒ of pixels in the projection domain. [18][19][20][21][22][23][24][25][26][27][28] Geometric calibration consists of two stages: ͑i.͒ characterization of pose across the range of source-detector orbit; and ͑ii.͒ correction of geometric nonidealities in the process of 3D reconstruction. Methods of pose characterization include the use of stereoscopic tracking systems to monitor mechanical motion 25 and, more commonly, image-based methods that operate directly on projection data acquired either from a prior calibration 2,18,23,24 or simultaneous with imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Points along 2D-vessel centerlines are manually indicated and fit using cubic splines [18]. In the current method, the points should be placed with sufficient frequency so that the straight-line segments connecting the points lie inside the vessel.…”
Section: Review Of the Multiple-view Self-calibration Techniquementioning
confidence: 99%
“…In a previous publication [18], we presented the multipleview self-calibration technique, which involves two steps: (1) calibration of the geometry, and (2) reconstruction of the 3D vessel centerline, as well as results of simulation and phantom studies. In simulation and phantom studies, we found that the average RMS difference between the pair-wise calculated 3D centerlines is approximately 7.5 mm prior to refinement (i.e., using the gantry information alone), whereas the average RMS difference is usually below 1 mm after refinement (using our multiple-view self-calibration technique).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation